2013
DOI: 10.1111/jawr.12038
|View full text |Cite
|
Sign up to set email alerts
|

Water Supply and Stormwater Management Benefits of Residential Rainwater Harvesting in U.S. Cities

Abstract: This article presents an analysis of the projected performance of urban residential rainwater harvesting systems in the United States (U.S.). The objectives are to quantify for 23 cities in seven climatic regions (1) water supply provided from rainwater harvested at a residential parcel and (2) stormwater runoff reduction from a residential drainage catchment. Water-saving efficiency is determined using a water-balance approach applied at a daily time step for a range of rainwater cistern sizes. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 29 publications
0
77
0
3
Order By: Relevance
“…A wider review of literature and RWH system design tools illustrates that appraisal beyond financial benefit is lacking [18][19][20]. An appraisal under a single objective "maximise whole-life financial benefit of water reuse" omits many of the nuanced benefits offered by RWH systems.…”
Section: Existing Cost-benefit Approaches To Rwh Assessmentmentioning
confidence: 99%
“…A wider review of literature and RWH system design tools illustrates that appraisal beyond financial benefit is lacking [18][19][20]. An appraisal under a single objective "maximise whole-life financial benefit of water reuse" omits many of the nuanced benefits offered by RWH systems.…”
Section: Existing Cost-benefit Approaches To Rwh Assessmentmentioning
confidence: 99%
“…One is the perspective of the water supply, mainly to discuss water supply management [8][9][10][11][12] and unconventional water resource utilization [13][14][15][16]. The other is the perspective of urban water demand, which mainly focuses on water conservation [17][18][19][20] and water use efficiency improvement [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A rainwater harvesting system not only reduces stormwater, but also provides an additional water resource. Steffen et al [16] showed that a 190-liter rain barrel installed for a household of four persons can provide a water saving efficiency of approximately 50% of the nonpotable indoor water demand in regions with higher annual precipitation. Walsh et al [17] evaluated rainwater harvesting systems of different capacities and identified that the 227-litter rain barrel is the most cost-effective in their case study location.…”
Section: Introductionmentioning
confidence: 99%